Phasing out of Environmentally Harmful Subsidies: Consequences of the 2003 CAP Reform - Markus F. Hofreither; Erwin Schmid; Franz Sinabell (Austrian Institute of Economic Research (WIFO), 2004)
Subsidies linked to production have been classified to be environmentally harmful by OECD. A core element of the EU 2003 Common Agricultural Policy (CAP) reform is to decouple income support from production. This paper estimates the environmental consequences of this policy reform. An agricultural sector model using a modified version of the positive mathematical programming method depicts the complex natural, structural, and political relationships of Austrian farming. Changes in management measures can be analyzed with respect to their environmental effects by using appropriate indicators. Simulation results show that the 2003 CAP reform will not only reduce average cost of production, but may also improve environmental conditions regarding soil, water, and greenhouse gases. Thus, this reform is likely to bring about outcomes which the previous CAP-reform (Agenda 2000) promised, but did not deliver.
Keywords: Q12; Q18; Q24; Q28; 330; Common Agricultural Policy reform; Environmental indicators; Agricultural sector model; De-coupled subsidies; EU-Agrarpolitik; Agrarsubvention; Reform; Umweltpolitik; Wirkungsanalyse; EU-Staaten